Analisis Kualitas dan Keamanan Pangan Sampel Terasi Melalui Uji Boraks dan Formalin di UPTD Laboratorium Keswan Kesmavet Sidoarjo - Nuris Khumairo; Nindira Cahya Listianti; Nurfadhilah Puspitasari; Sri Wardiyah khumairo; Hanik Faizah (Universitas Djuanda, 2025)
Borax and formalin are hazardous chemicals prohibited for use in food due to their potential to cause serious health problems, including organ damage and increased cancer risk. This study aimed to identify the presence of borax and formalin in six shrimp paste samples obtained from three traditional markets in Sidoarjo Regency. Qualitative testing was conducted using borax test kits with curcumin indicators and formalin test kits containing Fo-1 and Fo-2 reagents. Each sample was labeled from TR0 to TR5 and examined for color changes as indicators of the presence of these harmful substances. The results showed that all samples tested negative for both borax and formalin, indicated by the absence of color change in each test. These findings suggest that the tested shrimp paste samples meet food safety standards and are safe for consumption. This study highlights the importance of routine monitoring and rapid testing as essential measures to protect consumers from exposure to hazardous chemicals in traditional food products.